Long-Read Sequencing Annotation of the Transcriptome in DNA-PK Inactivated Cells - Song, Liwei; Yu, Mengjun; Jin, Renjing; Gu, Meng; Wang, Ziyu; Hou, Dailun; Xu, Shaofa; Wang, Jinghui; Ma, Teng (Frontiers in Oncology, 2022)
The DNA-dependent protein kinase catalytic subunit (DNA-PKcs) together with Ku80/Ku70 heterodimer constitutes the intact DNA-PK kinase, which is an upstream component of the DNA repair machinery that signals the DNA damage, orchestrates the DNA repair and serves to maintain genome integrity. Beyond its role in DNA damage repair, the DNA-PK kinase is also implicated in transcriptional regulation and RNA metabolism, with an illuminated impact on tumor progression and therapeutic responses. However, the effort to identify DNA-PK regulated transcriptome is limited by short-read sequencing to resolve the full complexity of the transcriptome. Therefore, we leveraged the PacBio Single Molecule, Real-Time (SMRT) Sequencing platform to study the transcriptome after DNA-PK inactivation to further underscore the importance of its role in diseases. Our analysis revealed additional novel transcriptome and complexed gene structures in the DNA-PK inactivated cells, identifying 8355 high-confidence new isoforms from 3197 annotated genes and 523 novel genes. Among them 380 lncRNAs were identified. We validated these findings using computational approaches and confirmatory transcript quantification with short-read sequencing. Several novel isoforms representing distinct splicing events were validated through PCR experiments. Our analyses provided novel insight into DNA-PK function in transcriptome regulation and RNA metabolism.